Human Recourses for Social Change: Promoting Women’s Empowerment Through Solidarity Economy Models in Afghanistan and Pakistan (Global Journal of Human-Social Science, 2025)
Women’s economic participation in fragile and conflict-affected contexts remains one of the most pressing development challenges of our time. In Afghanistan, the erosion of rights and restrictions on women’s mobility since 2021 have drastically reduced access to employment and livelihoods, while in Pakistan, entrenched structural barriers continue to confine many women to informal or unpaid work. Against this backdrop, solidarity economy models cooperatives, mutual aid networks, community finance schemes, and social enterprises offer alternative pathways to income generation, collective protection, and social recognition. This article explores how such models can promote women’s empowerment in Afghanistan and Pakistan when approached through the lens of human resources for social change. Drawing on recent literature and reports (2024-2025), the study conceptualizes HR not as a narrow administrative function but as a strategic set of practices participatory governance, peer-to-peer training, leadership development, and collective accountability that can institutionalize inclusion and equity within solidarity-based organizations. Comparative evidence shows that while Afghan women increasingly rely on community-led initiatives to sustain livelihoods under restrictive regimes, Pakistani women benefit from somewhat more enabling legal and institutional frameworks yet continue to face significant gender gaps. In both contexts, solidarity economy initiatives have enabled women to diversify income, build selfconfidence, and gain decision-making power, though sustainability challenges persist due to limited financing, market access, and policy support.